Surgical treatment of aortic aneurysms combined with coronary artery disease - I. I. Zhekov; V. I. Kravchenko; I. M. Kravchenko; H. A. Zinchenko; A. I. Perepeluyk; V. V. Vayda (Ukrainian Journal of Cardiovascular Surgery, 2018)
In recent years, the proportion of operations with combined pathology of aortic aneurysms and coronary artery disease has increased. The combined operative intervention of the aortic aneurysm with concomitant coronary artery disease over the past decades has become widespread. The outcome of such interventions in modern cardiac surgical centers is 15-30%. Reducing the duration of artificial blood flow and ischemic time for a myocardium is a major problem in order to reduce the operational risk and the likelihood of death in such operations.Purpose: to evaluate the effectiveness of surgical correction of aortic aneurysms in combination with the restoration of myocardial revascularization.Materials and methods. Starting from 01/01/2010 to 31/12/2017, 105 patients were treated for the correction of aortic aneurysm and associated coronary artery disease.Conclusions. In order to improve the immediate results of surgery in patients with aortic aneurysms and the associated coronary artery disease in the presence of suboclusions of the major coronary arteries, the first stage of the operation should be complete revascularization of the myocardium, followed by correction of aortic pathology.